A novel TBX19 gene mutation in patients with isolated ACTH deficiency from distinct families with a common geographical origin - Charnay, Théo; Mougel, Gregory; Amouroux, Cyril; Gueorguieva, Iva; Joubert, Florence; Pertuit, Morgane; Reynaud, Rachel; Barlier, Anne; Brue, Thierry; Saveanu, Alexandru (Frontiers in Endocrinology, 2023)
Isolated ACTH deficiency (IAD) is a life-threatening condition, particularly in the neonatal period, while a main consequence of undiagnosed isolated ACTH deficiency in survivors is cognitive impairment. TBX19 is involved in the differentiation and proliferation of corticotropic cells and TBX19 mutations are responsible for more than 60 % of neonatal cases of IAD. We describe a new variant of the main TBX19 transcript (NM 005149.3, c.840del (p.(Glu280Asp fs*27)), classified as pathogenic, whose pathogenicity is assumed to be due to nonsense mediated decay leading to non-expression of T-box transcription factor TBX19. Moreover we summarize the TBX19 mutations published as individual cases since our last large cohort. Interestingly, this pathogenic variant was identified in four patients from three apparently unrelated families. Two of these families were consanguineous, and after investigations all of three were discovered to have roots in the same mountainous region of northern Morocco, suggesting a founder effect. Early diagnosis, timely treatment (hydrocortisone therapy) and preventive education allowed normal development, growth and quality of life in all patients.